NILAI MORAL DALAM LAGU THANK YOU ALLAH KARYA MAHERZAIN DAN RELEVANSINYA DENGAN DAKWAH ISLAM - Adina Maulidia; Muzaiyanah; Dinda Sofya Umbu Nay; Sayidah Afyatul Masruroh; Robi’ah Machtumah MMalayati (Menara Tebuireng, 2021)
There are many Muslim musicians from abroad whose names are famous all over the world, one of these musicians is Maher Mustafa Maher Zain. Maher Mustafa Maher Zain or what we usually call Maherzain is one of the most famous Muslim musicians in the world. Many of Maherzain's religious songs are loved by people all over the world and one of them is from Indonesia. In his work, Maherzain himself has released 3 albums, the first album is the album Thank You Allah, then the second is the album Forgive me and the last is the album One. In the Thank You Allah album, there is a song that people are familiar with. This song is very popular with the people because this song really inspires the people. The song is entitled Thank You Allah which will be taken as research material in this thesis. Based on the background above, the researcher formulated the research problem into two, namely a. Moral values ​​in the song Thank You Allah by Maherzain, b. The relevance of the song Thank You Allah by Maherzain to Islamic da'wah. In this study, researchers used a qualitative approach with content analysis methods, descriptive qualitative content analysis.From the results of the analysis that has been carried out, the researcher has concluded that the moral values ​​contained in the song Thank You Allah by Maherzain consist of patience, gratitude, responsibility, forgiveness and compassion. Every moral value has good understanding and benefits for every human being. Meanwhile, the relevance of the moral values ​​contained in the song Thank You Allah by Maherzain to Islamic da'wah is devoted to a preacher. In this case a da'i must be able to have five qualities or moral values ​​which include patience, gratitude, responsibility, forgiveness and compassion. So that the da'i's preaching can run effectively and be well received by the community, besides that a preacher if he has these five moral values ​​will be able to become uswatun hasanah (good role model) for every mad'u.